La place de la conception des technologies éducatives dans les inégalités socionumériques d'usage - Simon Collin
Since the 1990s, the study of digital inequalities has undergone sustained theoretical and empirical development, consolidating its scientific basis and legitimizing its social relevance, including in education. However, it has mainly focused on the unequal ways educational actors use technologies. The upstream of digital inequalities, that is, the role of design in the making of digital inequalities in education, has yet to be explored. The objective of this theoretical article is to clarify the relationship between the design of educational technologies and the digital inequalities of use to better understand how the former contributes to the latter. To do so, we draw on the script metaphor elaborated by Madeleine Akrich (1987) and extended to power relations by the feminist studies of the Social Shaping of Technology (SST).